2009
DOI: 10.1097/lgt.0b013e31819308d4
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Colposcopic Grading for Detection of High-Grade Cervical Intraepithelial Neoplasia

Abstract: Objective To relate aspects of online colposcopic image assessment to the diagnosis of grades 2 and 3 cervical intraepithelial neoplasia (CIN2+). Methods To simulate colposcopic assessment, digitized cervical images were obtained at enrollment after acetic acid application from 919 women referred for equivocal or minor cytologic abnormalities into the ASCUS-LSIL Triage Study. For each, two randomly assigned evaluators from a pool of 20 colposcopists assessed images using a standardized tool on-line. We calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 25 publications
8
90
0
5
Order By: Relevance
“…12 In the study by Gupta et al also correlation between colposcopic findings and HPE results was seen in 90 (88.23%) patients which is also comparable with our study. 8 Meenakshi et al found 96% correlation between colposcopy and histology.…”
supporting
confidence: 81%
“…12 In the study by Gupta et al also correlation between colposcopic findings and HPE results was seen in 90 (88.23%) patients which is also comparable with our study. 8 Meenakshi et al found 96% correlation between colposcopy and histology.…”
supporting
confidence: 81%
“…Colposcopy impressions are subjective; according to degree of white epithelium, contour of surfaces, margins, and vascular patterns. In cases of CIN 2-3, colposcopy missed to diagnose at the rate of underestimation was 57%, and the overestimation rate by Reid Index scoring was 70% (Massad et al, 2009;Stoler et al, 2011). Recent systematic review and meta-analysis stated that colposcopic biopsies yielded a sensitivity of 81.4% and specificity of 63.3% for CIN2-3 detection (Underwood et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the sensitivity of colposcopy at low thresholds was high (74.5%), but the specificity was lower at 57.5%. 10 The performance and accuracy of colposcopy depends largely on the training, experience, and skills of the colposcopist. Hence, sensitivity and specificity of colposcopy varies widely among studies in different parts of the world.…”
Section: -6mentioning
confidence: 99%